Determinación de la calidad de absorción visual de las unidades del paisaje del centro experimental Salache UTC, propuesta de conservación, 2022. - Luna Villacís, Evelyn Gabriela (2022)
This research project was developed with the purpose of assessing the visual quality and visual absorption capacity of the landscape of the Salache Experimental and Academic Center, located in the Province of Cotopaxi, in the Eloy Alfaro parish, Salache Bajo neighborhood; The methodology applied was based on the guidelines established by the Bureau of Land Management (BLM) method, which allowed assigning qualitative and quantitative values according to the numerical weighting scales focused on the determination of the components (relief, vegetation diversity, erodibility, erodibility, erosion, erosion, and visual absorption capacity of the landscape), diversity vegetation, erodibility, soil-vegetation contrast, vegetation regeneration, contrast, color, rock, soil, anthropization) that are part of the landscape units based on subjective assessments presented by the researcher through the analysis of photographs taken in the study area; field visits and surveys were carried out in order to get to know the opinions in a direct way. The results obtained from photographs 1, 2, 3 and 7 are within class B which mentions areas of medium quality, areas whose features have variety in shape, color and line, but which are common in the region studied and are not exceptional, on the contrary, photographs 5, 6 and 8 are in class C which mentions areas of low quality and therefore require restoration in their landscape units, On the other hand, the visual absorption capacity of the 8 photographs showed that they are in class I, which means that the landscape is very fragile, areas of high slope and difficult to regenerate. Based on these results, conservation, regeneration and maintenance activities were proposed for the area of incidence through the incorporation of endemic plant species that allow establishing management and conservation alternatives for the components that are part of the landscape units.